2022
DOI: 10.1186/s12877-022-03296-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of the concurrent use of anticholinergics for the motor symptoms of Parkinson’s disease and acetylcholinesterase inhibitors in Parkinson’s disease patients with dementia: a cross-sectional study using Korea National Health Insurance claims data

Abstract: Background The concurrent use of anticholinergics and acetylcholinesterase inhibitors (ACHEIs) in Parkinson’s disease (PD) patients with dementia should be avoided because the opposing pharmacological actions of both drugs reduce the treatment efficacy. We aimed to investigate the prevalence of the concurrent use of these two types of drugs in Korean patients. Methods In the 2017 Health Insurance Review and Assessment Service–National Aged Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…AChE inhibition is also considered as a remedial strategy for other types of neuronal disorders like dementia and Parkinson's diseases. Many Schiff bases synthesized in various parts of the world have been evaluated for anti-amnesic and anti-Alzheimer's activity with excellent activities [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…AChE inhibition is also considered as a remedial strategy for other types of neuronal disorders like dementia and Parkinson's diseases. Many Schiff bases synthesized in various parts of the world have been evaluated for anti-amnesic and anti-Alzheimer's activity with excellent activities [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, exposure to OPPs inhibits AChE activity via phosphorylation of the hydroxyl group of serine at the active site (7). Recent studies have shown that AChE activity and, therefore, acetylcholine levels change in patients with PD (8,9). These pesticides can also inhibit paraoxonase-1 (PON1) activity (10).…”
Section: Introductionmentioning
confidence: 99%